PENGARUH KEPEMIMPINAN, PENGAWASAN, DAN KOMPENSASI TERHADAP DISIPLIN KERJA PEGAWAI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA DAERAH (BKPSDMD) KABUPATEN KERINCI: MOHD. AFANDI, S.SOS - MOHD AFANDI (JURNAL ADMINISTRASI NUSANTARA, 2020)
This study aims to determine the effect of independent variables on the dependent variable. The object of this research is the Staff of the Regional Human Resources and Human Resources Development Agency (BKPSDMD) of Kerinci Regency. The number of samples in this study were 65 respondents. The analysis technique used is multiple linear regression. The results obtained by the partial test (t test) obtained: (a) There is a positive and significant influence of leadership on work discipline. (b) There is a positive and significant influence of supervision on work discipline. c) There is a positive and significant effect of compensation on work discipline. The results of the study simultaneously showed that leadership, supervision and compensation had a positive and significant effect on work discipline. And based on the Determination coefficient test (R2) the value was 0.658 or 65.8%. This indicated that the percentage contribution of the independent variable was leadership, supervision and compensation of the variables dependent Work Discipline of 0.658 or 65.8%. While the remaining 34.2% is influenced by other variables outside this study.